(untitled) (Annals of Medical Research, 2022)
Aim: In this prospective, randomised, clinical study; we aimed to compare the effects of endotracheal intubation (ETI) via direct laryngoscope (DLS) and fiberoptic bronchoscope (FOB) on intraocular pressure (IOP) and hemodynamic data of non-ophthalmic patients. Materials and Methods: Fifty-four adult patients undergoing non-ophthalmic surgeries performed in the supine position under general anesthesia requiring orotracheal intubation were included into the study. The patients were randomly and prospectively divided into 2 groups: Group DLS (n=27) and Group FOB (n=27). Mean arterial pressure (MAP), Heart rate (HR), IOP were measured at before induction (basal), post-induction and 1st, 2nd, 3rd, and 5th minutes of intubation. Results: There was no statistically significant difference in distribution of patient characteristics. Duration of intubation was significantly longer in Group FOB (p<0.001). There was no statistically significant difference in MAP and HR when groups compared each other. Statistically significant increase was found in IOP at 1st minute of intubation in Group DLS when compared with Group FOB (p<0.001). No significant difference was found in terms of IOP in other time periods. Conclusions: We thought that endotracheal intubation by FOB could be more useful with respect to endotracheal intubation by DLS in patients with high IOP due to significantly less rise caused in IOP when performed by experienced anesthesiologists.